Asthma mortality: comparison between New Zealand and England. Issue 6558 (22nd November 1986) - Sears, M R; Rea, H H; Rothwell, R P; O'Donnell, T V; Holst, P E; Gillies, A J; Beaglehole, R
Abstract : Causes for the high mortality from asthma in New Zealand were investigated by comparing deaths from asthma in caucasian subjects aged 15-64 in New Zealand with those from asthma in the same age group in two regions in England. There were no significant differences in the accuracy of death certification. The verified asthma mortality in New Zealand (4.2/100, 000) was over twice that in England. Many characteristics of patients and management, including poor compliance with treatment and deficiencies in long term and emergency care, were qualitatively similar in the two countries. New Zealand had an apparently higher rate of non-preventable deaths from asthma, suggesting a greater severity of asthma in New Zealand. In both countries, however, most deaths were associated with poor assessment, underestimation of severity and inappropriate treatment (over-reliance on bronchodilators and underuse of systemic corticosteroids), and delays in obtaining help. A greater frequency of some of these deficiencies in management remains a possible additional explanation for part of the excess mortality in New Zealand.